Analysis of barter modalities, equity and financing of inputs in soybean cultivation in Brazil - Trentin, Daniel; Menezes Filho, Antonio Carlos Pereira de; Ventura, Matheus Vinicius Abadia (Brazilian Journal of Science, 2022)
In the agricultural scenario, the agribusiness market is an important source of income, and it is an essential mechanism for generating employment for a large part of the population, in addition to being one of the main sources of wealth for a nation. In this scenario, the production of soybean (Glycine max L.) has great notoriety in Brazil, and in the world, due to its importance and impact on environmental, economic and social aspects. Despite its relevance, the generation of income from agriculture may be compromised due to the risks involved. In addition to the climatic and production risks involved in this activity, there are also market risks, more specifically, the risk of price fluctuations. The rural producer is increasingly in contact with information, technologies, and improvements and, consequently, inserted in a more competitive and risky market. Its income and its permanence in this system are linked to the effective management of these risks. In this sense, risk management in agriculture is increasingly based on two types of risk: price (market) and production. The main credit models for the agricultural producer in the acquisition of inputs can be separated into three: own capital, third-party capital, and Barter operation, each of these resources being offered by different systems. Equity originates from the results of previous harvests and new investments; third-party capital can be sourced from bank loans or credit cooperatives, and the third barter modality, the purchase of inputs where payment is made in installments through the exchange of grains. Given this context, the present review study sought to raise ideas on how to analyze the barter, equity, and financing of inputs in soybean cultivation in Brazil. These soy commercialization modalities are practiced all over the world, with great participation of Brazil. Therefore, the results obtained in this study indicate possible directions for managers and companies in the agribusiness sector.